Prolactin and macroprolactin levels in psychiatric patients receiving atypical antipsychotics: A preliminary study - Park, Young-Min; Lee, Seung-Hwan; Lee, Bun-Hee; Lee, Kyu Young; Lee, Kye-Seong; Kang, Seung-Gul; Lee, Hwa-Young; Kim, Won (Psychiatry research, 2016)
The aims of this study were to clarify whether atypical antipsychotics can elevate serum levels of both macroprolactin and prolactin, and whether the macroprolactin levels differ according to the type of atypical antipsychotic being taken. In total, 245 subjects were enrolled consecutively in 6 hospitals. Serum prolactin and macroprolactin levels were measured at a single time point during maintenance antipsychotic monotherapy. The mean total serum prolactin levels including macroprolactin were 11.91, 20.73, 16.41, 50.83, 12.84, and 59.1ng/mL for patients taking aripiprazole, blonanserin, olanzapine, paliperidone, quetiapine, and risperidone, respectively, while those for macroprolactin were 1.71, 3.86, 3.73, 7.28, 2.77, and 8.0ng/mL. The total prolactin and macroprolactin levels were significantly higher among those taking paliperidone and risperidone than among those taking any of the other antipsychotics (p<0.01). Moreover, there was a strong positive correlation between serum levels of prolactin and macroprolactin. Sexual dysfunction was reported in 35.5% (87/245) of the total subjects. However, the total prolactin level did not differ significantly between subjects with and without sexual dysfunction except gynecomastia. These findings suggest that treatment with risperidone and paliperidone can induce hyperprolactinemia and macroprolactinemia in psychiatric patients. •The aims of this study were to clarify the relationship between macroprolactin and prolactin.•Treatments with risperidone and paliperidone can induce hyperprolactinemia and macroprolactinemia.•Measuring macroprolactin levels seems to be important in patients with hyperprolactinemia.